PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT WAHANA GRAHA MAKMUR - Malini, Cantika Putri; Firmansyah, Firmansyah; Robain, Wilchan (International Conference on Humanity Education and Society (ICHES), 2024)
This research was conducted to find out how the influence of work discipline and work motivation on employee performance at PT Wahana Graha Makmur. The population in this research were all employees of PT Wahana Graha Makmur, totaling 81 employees. The number of samples taken was the population, namely 81 karyawants. This research was conducted from January to June 2024. This research used quantitative data processed with SPSS 24.0 with multiple linear regression method. The results showed that work discipline and work motivation either partially or simultaneously had a positive and significant effect on the performance of employees of PT Wahana Graha Makmur. Work discipline was the most dominant variable affecting performance. 91.1% of performance could be explained and obtained from work discipline and work motivation while the rest by other factors. Performance had a very strong relationship to work discipline and work motivation